FISHERY CRIME IN WETLAND ENVIRONMENT - Mispansyah, Mispansyah; Nurunnisa, Nurunnisa; Ratomi, Achmad; Fahmanadie, Daddy (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2019)
The aim of this research is first, to find out the characteristic of crimein Wetland Environment in Hulu Sungai Utara Regency. Secondly, to know the description of law enforcement in the Wetland Environment Area in Hulu Sungai Utara Regency. The method of this research is normative law research supported by field data (sociolegal research). The result of the research shows the characteristic of criminal acts in the environment, which is the Illegal Fishing of small fishermen by using the stun device with the transportation of boats conducted in the river, lake, and swamp areas. Illegal Fishing Crime is done to meet the needs of daily economic life. The law enforcement on illegal fishing, conducted by preventive efforts by the way of socialization to the community both collectively and individually, both organized and situational at the scene. Repressive efforts are conducted in 2 (two) forms: (1) through the process outside the judiciary and (2) in the judiciary. The process outside of the judiciary is conducted through criminal mediation based on police discretion, whereas through the judicial process is carried out by the process of investigation followed by prosecution and criminal detention through a court decision.